Peluruhan Batang Graphite Baterai Bekas Dengan Metode Electrochemical Expoliation Menggunakan Pelarut Asam Sulfat Dan Sodium Sulfat Untuk Produksi Graphene - Azhari Harahap; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Graphene is two dimensional material (2D) consisting of carbon atoms with a flat lattice configuration in a flexible hexagonal pattern. One of the materials that can be used as raw material in graphene synthesis is carbon used battery bar. The purpose of this research was to synthesize graphene using electrochemical exfoliation graphite (EEG) method and to study the process of exfoliation rate over 30, 60, 90, 120 and 150 minutes for 2.5 hours. Graphene was synthesized by using two solvents H2SO4 and Na2SO4 with varied concentrations of : 0.25 M, 0.5 M, 0.75 M and 1 M. From the synthesis results, the best exfoliation rate and the best yields were shown by Na2SO4 solvent at 1 M concentration with a yield of 21.83%. From the graphene conductivity test, the best conductivity was obtained by Na2SO4 solvent at 1 M concentration with conductivity value of 0,1698 Ω-1.cm-1.Key words : Electrochemical exfoliation graphite, graphene, graphite.